Kelayakan Ekonomi Alat Tangkap Ikan Bandrong Cakalang di Perairan Dangkal - Andi Adam Malik; Andi Sitti Halimah (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
The district waters of Barru, South Sulawesi have enormous fishery potential and taken by various fishing gears. One of the fishing gears is the Cakalang bandrong (skipjack tuna blanket net) which is a fishing gear modified by the local community, catch large pelagic fish in shallow water. This study aims to determine the economic feasibility of the skipjack tuna blanket net used by fishermen in the shallow waters Barru. Data collection was carried out through interviews with bandrong owners and fishermen, while observations were made on 3 units of Cakalang bandrong fishing gear and methods. The results showed that the NPV and B/C ratio>1, IRR> 12% interest rates, with a payback period of less than 2 years, so that the fishing using the skipjack tuna blanket net fishing gear is considered profitable, so it is feasible to be developed.